INFLUENCE OF DIETARY INCLUSION OF SUNFLOWER (Helianthus annus) OIL ON GROWTH PERFORMANCE AND OXIDATIVE STATUS OF BROILER CHICKS - Agubosi, O.C.P.; Alexander, James; Alagbe, J.O (Journals Park Publishing, 2022)
A study was conducted to evaluate the dietary inclusion levels of Sunflower oil (SFO) on the growth performance and oxidative status of broiler chicks. A total of one hundred and fifty (150) day old Abor acre chicks were randomly allotted into five dietary treatments in a completely randomized design (CRD). Each treatment was replicated thrice with ten birds per replicate. A basal diet was formulated to meet the nutrient requirement of broiler chicks. Birds on treatments 2, 3,4 and 5 were fed the basal diet mixed with 0.1, 0.2, 0.3 and 0.4 mls of sunflower oil, respectively while birds on treatment 1 was fed the basal diet with Oxytetracycline at 1.2g/kg. Feed and clean water were provided ad libitum throughout the experimental period which lasted for 28 days. Data were collected on average daily feed intake (ADFI), average daily weight gain (ADWG), feed conversion ratio (FCR) and oxidative status. Results on phytochemical composition of sunflower oil revealed the presence of alkaloid (3.86 %), condensed tannins (0.96 %), hydrolysable tannins (9.86 %), phenols (7.06 %), terpenoids (5.10 %), steroids (4.47%), saponins (3.51%) and flavonoids (10.06 %). ADWG, ADFI and mortality values were significantly (P<0.05) different in all the parameters measured. Birds fed 0.2, 0.3 and 0.4 mls of sunflower oil had similar final body weight gain, average weight gain and feed conversion ratio which is significantly (p<0.05) higher than those fed 0.1 mls of sunflower oil. Similarly ADFI of birds fed 0.2mls of sunflower oil was significantly (P<0.05) higher than those fed 0.1, 0.3 and 0.4mls. Activities of superoxide dismutase (SDA), glutathione peroxidase (GPx), catalase (CAT) and malonyldialdehyde (MLA) were significantly (P<0.05) influenced by the treatments. It can be concluded that the better performance observed in birds fed sunflower oil could be attributed to the activities of bioactive chemicals contained in sunflower oil which has been proven to stimulate functions of the intestinal tract to improve digestive secretions and scavenge free radicals.
Keywords: Antibiotics; Helianthus annus; Phytochemicals